The role of institutional ownership and industry characteristics on the propensity to pay dividend: An insight from company open innovation - S. Martono; Arief Yulianto; Rini Setyo Witiastuti; Angga Pandu Wijaya (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The purpose of this study is to test the free cash flow agency theory hypothesis; namely, (a) whether differences in industrial sector affect a company's propensity to pay dividends, and (b) whether institutional ownership is able to substitute for the propensity to pay dividends as a bonding mechanism. The analysis uses logistic regression to explore the existence of institutional ownership as a substitute for paying cash dividends in companies belonging to different industrial sectors. The results show that companies in the manufacturing sector have a greater propensity to pay dividends compared to those in non-manufacturing sectors. The results also indicate that low institutional ownership, as an external monitoring mechanism, can substitute for increasing the propensity to pay dividends. Overall, the results are consistent with implications in dividend policy. The results support the notion that the propensity to pay dividends accommodates different behavioral factors, considering sectoral differences. In addition, the results illustrate the relevance of alternative theories in explaining dividend policy from the perspective of agency theory. The results show that sectoral comparisons, in addition to institutional ownership factors, play important roles in the propensity of Indonesian companies to pay dividends. This study shows that each industry sector has different income characteristics, which affect the differences in propensity to pay dividends.
Keywords: 650; propensity to pay dividend; industry sectors; Institutional ownership